COVID-19 Neurological Manifestations and Underlying Mechanisms: A Scoping Review - Wenting, Angela; Gruters, Angélique; van Os, Yindee; Verstraeten, Sonja; Valentijn, Susanne; Ponds, Rudolf; de Vugt, Marjolein (Frontiers in Psychiatry, 2020)
Background: In the Corona Virus Disease 2019 (COVID-19) pandemic, the primary problem is respiratory-related, but there also is increasing evidence of central nervous system (CNS) involvement. This study aims to summarize the literature on neurological manifestations of COVID-19, underlying mechanisms of CNS involvement and cognitive consequences. Methods: A scoping review was conducted with multiple searches in PubMed, PsycInfo and CINAHL databases. Full text articles in English were included if they involved humans with COVID-19. The search was updated twice, the latest on 19 May 2020. Results: After screening 266 records and cross referencing, 85 articles were included. The articles were case studies, opinion papers, letters to editors and a few observational studies. No articles were found regarding cognitive consequences in COVID-19 patients. All reported on neurological manifestations and/or underlying mechanisms of CNS involvement in COVID-19. Conclusion: Neurological manifestations of COVID-19 vary from mild (e.g. loss of taste and smell, dizziness, headache) to severe (e.g. ischemic stroke, encephalitis). Underlying pathways are suggested to be both indirect (as a result of thrombotic complication, inflammatory consequences, hypoxia, blood pressure dysregulation), and direct (neurotropic properties of the virus). Since most articles were opinion papers and no studies have been conducted on cognitive consequences, further research is warranted.